Mechanical Effects of Lining Thinning in Shallow Four-Track High-Speed Railway Tunnels: Field Monitoring and Numerical Analysis - Shaohui He; Bo Jiang; Jianfei Ma (Applied Sciences)
Lining thinning is a common defect in railway tunnels; however, its impact on shallow four-track high-speed railway (HSR) tunnels—particularly on rock pressure—remains poorly understood. This study investigates the influence of lining thinning on the genuine pressure (also referred to as “deformation pressure”) of such tunnels through field investigation, long-term monitoring, and numerical simulation. Firstly, a lining thinning survey was conducted across ten tunnels, and the statistical distribution of defect parameters was analyzed. Second, over 180 days of field monitoring were carried out in China’s first four-track HSR tunnel (XBS Tunnel) to evaluate the rock pressure state. Third, a three-dimensional numerical model was developed to evaluate the effects of lining thinning and structural degradation on the principal stress, deformation, and genuine pressure of shallow four-track HSR tunnels. The results indicate that thinning defects are widespread, with 38.64% occurring at the vault and over 84% having minimum thicknesses below 0.26 m. The actual rock pressure in the XBS Tunnel was significantly lower than theoretical predictions, and the tunnel primarily experienced genuine pressure rather than loosening pressure during construction, with the secondary lining serving as a safety reserve. Lining thinning leads to stress redistribution and concentration, weakens structural stiffness, and increases the likelihood of damage. It also induces a transition from genuine pressure to loosening pressure, a process that is further accelerated by surrounding rock and lining degradation. The findings provide important insights for the evaluation, design, and long-term maintenance of large-span HSR tunnels.